A non-linear causal network of marketing channel system structure. (March 2015) - Dost, Florian
Abstract: This article takes a systems perspective to study marketing channel system structure dynamics and their interactions with economic system dynamics. A novel, non-linear method from ecology is used to establish a causal network of mostly bi-directional causal forcing between economic variables and marketing channel system structure. This resulting causal network facilitates a comprehensive understanding of a marketing channel system. The study finds a highly endogenous and non-linearly interrelated subsystem encompassing online/offline retail channel structure, retail/wholesale channel structure, the ratio of import to consumption and the competitive dynamics of the economic system. Surprisingly, marketing channel system structure is rather resilient to changes in economic growth. In contrast, changes in retail/wholesale channel structure affect economic growth. The results may help to caution marketing managers changing their marketing channel structures too routinely. Moreover, the identified causal network presents a starting point for further empirical marketing channel system analyses. Implications particularly affect future empirical marketing channel system studies based on linear structural models. Graphical abstract: Highlights: We propose using a novel non-linear method to uncover the causal network of marketing channel system structure dynamics. Marketing channel system structure, competitive dynamics, and the import to consumption ratio all interact in a highly interrelated, endogenous and therefore non-linear subsystem. Marketing channel system structure is an antecedent to but not a direct consequence of economic growth.